(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Escherichia coli strain ATCC 8739 is an important strain of pharmaceutical and biotechnological industries. We studied the viability of culture suspension of Escherichia coli strain ATCC 8739 at 2 to 8°C up to 360 days in 0.9% w/v NaCl. The culture suspension containing 10000 cfu/ml used in the study was stored at 2 to 8°C for 360 days in 0.9% w/v NaCl. Using 10µl of above culture suspension, the viable count was made by the pour plate technique using Soyabean Casein Digest Agar medium in fixed interval of time during the 360 days storage period. During the storage period, population of Escherichia coli strain ATCC 8739 decreased from 10000 cfu/ml to 9900 cfu/ml during the first 30 days, whereas the population decreased to 0 cfu/ml in 360 days. Findings emanate from the study indicates that 30 days storage period of Escherichia coli strain ATCC 8739 at 2 to 8°C in 0.9% w/v NaCl is suitable for laboratories testing purposes on account of fact that in 30 days storage period, population of Escherichia coli strain ATCC 8739 decreased from 10000 cfu/ml to 9900 cfu/ml which is very low.